Model Pengembangan Literasi Teknologi Guru Pada Pembelajaran Berbasis Digital - Sudarjat, Jaja; Anwar, Wawan Syahiril; Suchyadi, Yudhie; Indriani, rini Sri; Amani, Gita Salwa Nisrina (Universitas Pakuan, 2025)
Teacher Technology Literacy Development Model in Digital Based LearningMastery of technological literacy for teachers is part of competency and plays a very important role in the era of Industrial Revolution 4.0. Reading and writing literacy is the most basic literacy that a teacher must master, in order to master other basic literacies. In developing students' writing skills, teachers should ideally have adequate writing skills. With skills in the field of writing, a teacher is expected to be able to have an impact on students' writing abilities so that ultimately the teacher's abilities in the field of writing will produce students with good character and the ability to create. However, it is unfortunate that teachers' abilities in the field of writing still do not meet expectations. Many teachers do not have the ability to write and it is not uncommon for teachers to think that writing is difficult. The low use of the internet in the world of education is also the background to the lack of education on the proper use of digital technology, resulting in misuse of digital technology such as cyberbullying, privacy violations, hoaxes, pornographic content and violence. This misuse is considered a problem in today's digital society due to the low culture of technological literacy. To overcome these negative impacts, an adequate technological literacy culture is needed. Teachers must have good understanding and creative thinking skills, especially in solving various learning problems. Thinking skills and scientific processes must be developed through learning with certain models and media to develop teachers' ability to think creatively, innovatively and productively. The use of multimedia media is a very effective medium for learning, it will help students to find answers with their own efforts based on their abilities and creative thinking skills. The benefits of multimedia media in learning are that it makes the learning process more interesting, more interactive, the quality of learning can be improved, and the teaching and learning process can be carried out anywhere and at any time, and students' learning attitudes can be improved. The aim of the research is to improve teachers' understanding abilities and creative thinking skills in the learning process. The research subjects were teachers at Nurul Iman Islamic Elementary School, Bogor Regency. The research design used is that teachers will divide groups into small groups with 4-5 members in each group. During the learning process, observations regarding the teacher's cooperation when learning with multimedia media are carried out to assess their understanding abilities and creative thinking skills. The observation results of each cycle are evaluated as material for reflection in the next cycle to improve the teacher's understanding and creative thinking skills in accordance with the targets that have been set.